From “The way of life” to “The code of thoughts”: problems of reconstruction of Leo Tolstoy’s religious-philosophical worldview - Nadezda Kasavina; Yury Prokopchuk; Ksenia Semenova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article discusses the history of the creation of the "Code of Thought of Leo Tolstoy", which reflects the writer's system of views and reconstructs the religious and philosophical foundations of his work. This literary and philosophical monument began to be created during Tolstoy's lifetime and with his participation, the process of collecting and systematizing the thoughts of the classic took several decades. The Code presents various aspects of the writer's religious, philosophical, moral, and aesthetic views. The sources of the Code are Tolstoy's artistic, philosophical and journalistic works. The study of the stages of the evolution of the thinker's worldview shows a clear tendency to create metatexts that reflect all the facets of his religious and philosophical teaching. However, the "Code of Thoughts" was never published, despite the efforts of Tolstoy's closest disciples and followers. The authors of the article trace the influence of the structure of the writer's last collection of thoughts "The Way of Life" on the overall content composition of the "Code of Thoughts", showing that it was it that was taken as the basis for the formation of the text setting forth the main features of Tolstoy's worldview. With the help of archival sources introduced into scientific circulation (documents from the funds of V.G. Chertkov, N.N. Gusev and others), the authors made an attempt to clarify the features of the work on this monument, to show the influence of the socio-cultural, political context, life circumstances that prevented the publication of "The Code of Thoughts of L.N. Tolstoy", which was supposed to become a bright page in Russian philosophical thought. "The Way of Life" was a guideline for the creators of the "Code of Thoughts", which was a way of religious and philosophical conceptualization of the writer's heritage, the key foundations of his consideration of man, spiritual life, social and cultural changes. The work shows the importance of this work, which has not yet been published, for understanding the history of Russian culture, for the interpretation of topical problems of modern Tolstoy studies. The methods found for reconstructing the worldview architectonics of the "Code of Thoughts" can be the basis for continuing its study and further work on preparing for publication a monument that resurrects the work and aspirations of both the writer himself and his like-minded people.